Pengaruh Kepemimpinan dan Komunikasi Terhadap Kinerja Karyawan pada Pabrik Gula (PG) Kebon Agung Malang - JawaTimur - Hironimus Hironimus Wanda; Sri Sri Wilujeng; Arien Anjar Puspitosari Suharso (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2018)
Human resource management is the development of an integrated process in management consisting of planning, organizing, directing and supervising resources within the organization. The success of an organization is a very important factor that is in an organization or company, in this case human resources have an important role both individuals and groups, and human resources is one of the main movers in the smooth running of an organization's activities, back and forth of a organization is determined by human resources. This study uses quantitative with a sample of 100 employees in the Sugar Factory (PG) KebonAgung Malang, East Java. Measurement of variables using a Likert scale with a score scale of 1 to 5. Data were analyzed using multiple linear regression statistical techniques. The results of the study together there is a significant influence between the variables of Leadership and Communication on Employee Performance and partially positive and significant leadership support on employee performance. This gives a good picture of leadership which will achieve high levels of performance, while the number of employees with poor leadership will also lower performance. The results showed a positive and significant communication variable on employee performance. This relates to the lack of communication, both horizontal communication and vertical communication will achieve low performance.